Urinary CD8+HLA-DR+ T Cell Abundance Non-invasively Predicts Kidney Transplant Rejection - Grothgar, Emil; Goerlich, Nina; Samans, Bjoern; Skopnik, Christopher M.; Metzke, Diana; Klocke, Jan; Prskalo, Luka; Freund, Paul; Wagner, Leonie; Duerr, Michael; Matz, Mareen; Olek, Sven; et al. (Frontiers in Medicine, 2022)
Early detection of kidney transplant rejection remains a challenge in patient care. Non-invasive biomarkers hold high potential to detect rejection, adjust immunosuppression and monitor kidney transplant patients. So far, no approach has fully satisfied requirements to innovate routine monitoring of kidney transplant patients. In this two-center study we analyzed a total of 380 urine samples. T cells and tubular epithelial cells were quantified in kidney transplant patients with graft deterioration using flow cytometry. Epigenetic urine cell quantification was used to confirm flow cytometric results. Moreover, a cohort of KT patients was followed up during the first year after transplantation, tracking cell subsets over time. Abundance of urinary cell counts differed in patients with and without rejection. Most strikingly, various T cell subsets were enriched in patients with T cell-mediated rejection (TCMR) compared to patients without TCMR. Among T cell subsets, CD8+HLA-DR+ T cells were most distinctive (AUC = 0.91, Spec.: 95.9%, Sens.: 76.5%). Epigenetic analysis confirmed T cell and tubular epithelial cell quantities as determined by flow cytometry. Urinary T cell abundance in new kidney transplant patients decreased during their first year after transplantation. In conclusion urinary T cells reflect intrarenal inflammation in TCMR. T cell subsets yield high potential to monitor kidney transplant patients and detect rejection. Hereby we present a promising biomarker to non-invasively diagnose TCMR.